SrCo0.8Ti0.1Ta0.1O3-δ perovskite: A new highly active and durable cathode material for intermediate-temperature solid oxide fuel cells - Gu, H.; Xu, M.; Song, Y.; Zhou, C.; Su, Chao; Wang, Wei; Ran, R.; Zhou, W.; Shao, Zongping (ELSEVIER SCI LTD, 2021)
Reducing the operating temperatures of solid oxide fuel cells (SOFCs) to the intermediate-temperature range (IT, 400–650 °C) can bring about several benefits including cost effectiveness, prolonged lifetime and flexible sealing. Nevertheless, the accompanying deterioration of cathodic activity for oxygen reduction reaction (ORR) introduces a large obstacle for commercial applications of IT-SOFCs. Herein, a new perovskite SrCo0.8Ti0.1Ta0.1O3-δ (SCTT) is developed by co-doping titanium and tantalum into the B-site of parent SrCoO3 oxide, which may tackle this problem. At 400–650 °C, SCTT shows high electrical conductivities (65–142 S cm−1), appropriate oxygen vacancy concentrations (0.23–0.27) and high bulk diffusion capability due to a synergy between the two dopants in SCTT. Consequently, SCTT exhibits a favorable ORR activity with an area-specific resistance of only 0.17 Ω cm2 at 500 °C on samaria-doped ceria electrolyte, and the corresponding cell generates a high peak power density (PPD) of 0.90 W cm−2 at 500 °C with negligible performance decay for 180 h. Additionally, SCTT performs well in protonic ceramic fuel cells, achieving a PPD of 0.78 W cm−2 at 650 °C and a high durability for ~176 h at 550 °C. This work provides a new promising cathode material that may accelerate the commercialization of IT-SOFC technology.